2013
DOI: 10.1128/mcb.00025-13
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Snt2 Protein Coordinates the Transcriptional Response to Hydrogen Peroxide-Mediated Oxidative Stress

Abstract: dRegulation of gene expression is a vital part of the cellular stress response, yet the full set of proteins that orchestrate this regulation remains unknown. Snt2 is a Saccharomyces cerevisiae protein whose function has not been well characterized that was recently shown to associate with Ecm5 and the Rpd3 deacetylase. Here, we confirm that Snt2, Ecm5, and Rpd3 physically associate. We then demonstrate that cells lacking Rpd3 or Snt2 are resistant to hydrogen peroxide (H 2 O 2 )-mediated oxidative stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 68 publications
3
50
0
Order By: Relevance
“…Notably, bypass suppression was not seen upon deletion of PHO23 or SAP30, which encode more peripheral subunits of Rpd3L. Using the same approach, we also found that loss of the Rpd3m complex ( Figure 1A), through deletion of SNT2 (Baker et al 2013), did not bypass esa1Δ ( Figure 1C). In further characterization of bypass conditions, we focused on the SDS3 deletion as it proved to be a stronger suppressor of esa1Δ than dep1Δ ( Figure 1B).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Notably, bypass suppression was not seen upon deletion of PHO23 or SAP30, which encode more peripheral subunits of Rpd3L. Using the same approach, we also found that loss of the Rpd3m complex ( Figure 1A), through deletion of SNT2 (Baker et al 2013), did not bypass esa1Δ ( Figure 1C). In further characterization of bypass conditions, we focused on the SDS3 deletion as it proved to be a stronger suppressor of esa1Δ than dep1Δ ( Figure 1B).…”
Section: Resultsmentioning
confidence: 60%
“…Rpd3 was recently reported in a third complex, Rpd3m, along with the Snt2 and Ecm5 subunits ( Figure 1A) (Shevchenko et al 2008;McDaniel and Strahl 2013). This complex is enriched at promoter regions and has a role in the response to oxidative stress (Baker et al 2013), but little else is yet known about its function.Genetic, biochemical, and genome-wide studies suggest that Rpd3 and Hda1 are the most relevant opposing activities to Esa1 (Vogelauer et al 2000;Lin et al 2008;Chang and Pillus 2009); yet important questions remain. Rpd3 has been directly identified as the deacetylase for some histone and nonhistone targets of Esa1 (Lu et al 2011;Rando and Winston 2012;Yi et al 2012), whereas genetic interaction networks point to deletion of HDA1 as the most prominent alleviating hub for NuA4 (Lin et al 2008).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…MRB230 was previously called laeC by Butchko et al (14); however, AN9517 is a homolog of the yeast gene SNT2 (E3 ubiquitin ligase), which coordinates the transcriptional response to hydrogen peroxide stress (44,45). A ho-molog in the plant pathogen Fusarium oxysporum, Snt2, is required for full pathogenicity on muskmelon (46).…”
Section: Figmentioning
confidence: 99%
“…Both databases predict the presence of gene products smaller than the SNT2 homolog in Saccharomyces cerevisiae, A. fumigatus, and A. flavus. SNT2 is an E3 ubiquitin ligase that has been shown to localize to promoters of stress response genes and is involved in the ubiquitination and degradation of excess histones (44,45). SNT2 is observed to associate with histone-modifying enzymes in fission and budding yeasts (62).…”
Section: Fig 2 Gene Deletions Of Novel Regulators Inmentioning
confidence: 99%